2015
DOI: 10.3233/wor-151990
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal symptoms (MSS) and their associations with ergonomic physical risk factors of the women engaging in regular rural household activities: A picture from a rural village in Bangladesh

Abstract: BACKGROUND: Musculoskeletal complaints among housewives are very common around the world. In Bangladesh, although the majority of women are involved in various household activities, no studies were found related to musculoskeletal health and ergonomic risk factors for this work. OBJECTIVE: This study explored the prevalence of commonly affected body parts where the women experienced Musculoskeletal Symptoms (MSS), the disruption of normal activities due to the MSS, and the association of MSS with ergonomic phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 35 publications
2
14
0
10
Order By: Relevance
“…Mean age of participants ranged from 29 to 49 years across studies. Six studies included samples from high-income countries [ 47 – 52 ] and five studies were included samples from LMICs (Ghana/South Africa, Bangladesh, Sri Lanka, Brazil, Lebanon) [ 25 , 53 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mean age of participants ranged from 29 to 49 years across studies. Six studies included samples from high-income countries [ 47 – 52 ] and five studies were included samples from LMICs (Ghana/South Africa, Bangladesh, Sri Lanka, Brazil, Lebanon) [ 25 , 53 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mean age of participants ranged from 29-49 years across studies. Six studies included samples from highincome countries [48][49][50][51][52][53] and ve studies were included samples from LMICs (Ghana/South Africa, Bangladesh, Sri Lanka, Brazil, Lebanon) [25,[54][55][56][57].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Seven studies recruited only women [25,48,50,[52][53][54]57], three studies either had a sample that included at least 50% women or reported gender-strati ed results [49,51,55], and one large-scale study did not specify the number of women recruited but strati ed results by gender [56]. All studies speci ed common domestic tasks done by women (e.g.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations